Improving students’ writing skills by using mind-mapping assisted by MindMeister at the twelfth graders in SMA Negeri 2 Ujungbatu - Irdian Febri; M. Masyhud (Jurnal Pendidikan Profesi Guru, 2022)
The study focuses on improving students’ writing skills through a mind-mapping strategy assisted by the MindMeister application in writing news text. This classroom action research was conducted in two cycles. This study was held in SMA Negeri 2 Ujungbatu, Rokan Hulu Regency, Riau. The sample is 30 twelfth-grader students. The variable measured was students’ writing skills. The data was collected using a pretest-posttest, observation checklist, and questionnaire. The pre-test score was 59.57, while the post-test was 82.23. The writing test in the second cycle reached 78.22. The mind mapping assisted by the MindMeister application strategy can influence writing skills. The analysis of the questionnaire and observation also supported that the strategy is appropriate in teaching writing news text. The teacher should be creative and innovative to create enjoyable learning processes to motivate students in writing.